Cotton Plant Leaf Diseases: A Brief Survey - Chaliha, Anjali; Goyal, Saransh; Gupta, Kritagya; Udawant, Prashant (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Cotton is India's most significant cash crop. Among all cash crops in the country, it is also known as "White Gold" or "The King of Fibers." Leaf spot, aphid attack, jassid attack, and whiteflies account for 80-90 percent of illnesses that affect cotton leaves. A review on the location and order of cotton leaf illnesses is introduced in this review. Human eyes have difficulty identifying the specific sort of leaf disease that affects a plant's leaf. Consequently, picture preparing, and AI approaches can be gainful in appropriately distinguishing cotton leaf sicknesses. The photographs for this undertaking were taken utilizing an advanced camera in a cotton field.
Keywords: Aphid Attack; classification; image processing; jassid attack; leaf spot; plant disease detection; whiteflies